Formation of carbon nanotubes catalyzed by metal and bi-metal via pulsed laser depositon technique - Yahya, Noorhana; Beh, Hoe Guan; Lim, Kean Pah; Ismail, Ismayadi; Al-Habashi, Ramadan Masoud; Waji, Samalia Bawa; Shafie, Mohd Shamsul Ezzad; Mohd Saad, Mohd Hashim (Universiti Putra Malaysia Press, 2005)
Carbon nanotubes were formed by laser ablation using graphite containing a metal and bi-metal catalyst as a target. The Nd:YAG laser with 532 nm wavelength, 10.54 W was used to irradiate the target to form the carbon nanotubes. The pressure inside the chamber was kept at 4 Torr. Web-liked carbon nanotubes were found on the substrate after 30 minutes laser irradiation. The SEM images showed that the diameter of the carbon nanotubes formed by metal and bi-metal catalyst in the ranging 35-150nm. The yield of carbon nanotubes depended on the metal catalyst, NiCo was found is an effective catalyst for the growth of Carbon nanotubes.